Odpowiedzi

2009-10-05T17:09:15+02:00
A)[(2/7)^3:(3/14)^3]:[(4/5)^3*(5/6)3]=
=[2/7*14/3]^3:[4/5*5/6]^3=(4/3)^3:(2/3)^3=(4/3*3/4)^3=1

b)(1 1/2)^3*(2/3)^3-(0,4 *2 1/2 )^5=(3/2)*2/3)^3-(2/5*5/2)^5=1-1=0

uporządkuj dane liczby malejąco:
(-1/2)^2 ; 4^0; (-2)^3; (1,25)^2; (-3)^4; -171^1; (2 1/3)^3; (0,1)^5


(-3)^4; (2 1/3)^3; (1,25)^2; 4^0; (-1/2)^2; (0,1)^5; (-2)^3; -171^1


Najlepsza Odpowiedź!
2009-10-05T17:17:35+02:00
A)[(2/7)³:(3/14)³]:[(4/5)³*(5/6)³] = [2/7*14/3]³:[4/5*5/6]³ = [4/3]³:[2/3]³=[4/3*3/2]³=2³=8

b)(1 1/2)³*(2/3)³-(0,4 *2 1/2 )⁵ = (3/2)³*(2/3)³-(2/5*5/2)⁵ = 1³-1⁵ = 1-1=0

uporządkuj dane liczby malejąco:
(-1/2)² = ¼=4/16
4⁰ = 1
(-2)³ = -8
(1,25)² = (5/4)²=25/16= 1 9/16
(-3)⁴=81
-171¹=-171
(2 1/3)³=(7/3)³=343/27 =12 19/27
(0,1)⁵=0,00001

(-3)⁴
(2 1/3)³
(1,25)²
4⁰
(-1/2)²
(0,1)⁵
(-2)³
-171¹